University Students’ Readiness to Adapt to the Change of Learning Platform during Campus Closure - Waluyo, Untung; Sudirman; Hakim, Mansur (Technium Social Sciences Journal, 2022)
The unprecedented change of the learning platform has forced university students adapt to new ways of learning. The present survey study aimed to reveal students’ readiness to adjust to such a situation. The population of the research was comprised of students of private and state universities in Lombok Island, Indonesia. A purposive sampling technique was used to select all respondents who studied through online platform. The data were gathered using an online survey questionnaire. To support the data findings from the survey, the researchers interviewed 8 participants from different participating universities. Findings of the study show that on the average the respondents had sufficient knowledge to use online information and technology, access digital literacy, and manage learning resources. The majority of the respondents had high expectations to explore the use internet literacy for their own learning. Yet, they received inadequate institutional supports. The mismatch between students’ expectations and the actual provision of the institutional services has potentially demotivated students to take part in the online classes. The study also reported that respondents experienced difficulties to participate in the online learning due to bad internet connection and additional financial burdens. Such difficulties had influenced the respondents’ choice of learning modes and readiness to take part in the online classes.